2020
DOI: 10.1002/prs.12207
|View full text |Cite
|
Sign up to set email alerts
|

Operational discipline in practice

Abstract: A general guideline to improve operational discipline is required. Operational discipline can be improved with simple things such as floor level meeting (FLM), job cycle check (JCC), risk assessment (RA), daily safety audit (DSA), consequence analysis (CA), mechanical integrity (MI), incident investigation (II), management of change (MOC), behavior observation (BO), pre-start up safety reviews (PSSR), process hazard analysis (PHA), job risk assessment (JRA), quantitative risk assessment (QRA), and process safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…These forms are shown in Figure 7. Incident investigation report form, floor level meeting form, consequence analysis form, job cycle check, mechanical integrity form, risk assessment work instruction wise, management of change form and daily safety audit form are presented in our earlier publication 18 which can be used as such or modified according to operations of a specific industry. Incident investigation report form 18 need to be completed after the incident and previous incidents may be investigated for learning and why tree analysis technique 19 may be used to identify which management systems failed during the incident.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These forms are shown in Figure 7. Incident investigation report form, floor level meeting form, consequence analysis form, job cycle check, mechanical integrity form, risk assessment work instruction wise, management of change form and daily safety audit form are presented in our earlier publication 18 which can be used as such or modified according to operations of a specific industry. Incident investigation report form 18 need to be completed after the incident and previous incidents may be investigated for learning and why tree analysis technique 19 may be used to identify which management systems failed during the incident.…”
Section: Introductionmentioning
confidence: 99%
“…Incident investigation report form, floor level meeting form, consequence analysis form, job cycle check, mechanical integrity form, risk assessment work instruction wise, management of change form and daily safety audit form are presented in our earlier publication 18 which can be used as such or modified according to operations of a specific industry. Incident investigation report form 18 need to be completed after the incident and previous incidents may be investigated for learning and why tree analysis technique 19 may be used to identify which management systems failed during the incident. Floor level meetings should be weekly and involve operators, engineers, senior engineers and in charges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of 400 operational incidents was reported by Rashid et al and concluded that process hazard analysis (PHA) has 16% share as a root cause or contributing factor in the considered incidents [8] . PHA role in enhancing operational discipline is discussed in another study [9] . In another work, Rashid et al has discussed significance of PHA, complications in performing PHA and hazardous scenarios which needs to be considered for conducting PHA [10] .…”
Section: Introductionmentioning
confidence: 99%